Deep Brain Stimulation Impact on Social and Occupational Functioning in Parkinson's Disease with Early Motor Complications. Issue 6 (3rd August 2020) - Stoker, Valerie; Krack, Paul; Tonder, Lisa; Barnett, Gillian; Durand‐Zaleski, Isabelle; Schnitzler, Alfons; Houeto, Jean‐Luc; Timmermann, Lars; Rau, Joern; Schade‐Brittinger, Carmen; Vidailhet, Marie; Deuschl, Günther; et al.
ABSTRACT: Background: Deep brain stimulation (DBS) improves motor symptoms and quality of life in patients with Parkinson's disease (PD) and early motor complications, suggesting that DBS could be prescribed to the working‐age PD population. Objectives: To investigate the effect of DBS compared with best medical therapy (BMT) on social, psychosocial, and occupational functioning in patients with PD ≤60 years of age with early motor complications, its correlates, and possible underlying rationale. Methods: Methods included analyses of the Social and Occupational Functioning Assessment Scale, Scales for Outcomes for Parkinson's–Psychosocial, Professional Fitness, Starkstein Apathy Scale, and Schwab and England Activities of Daily Living Scale from the EARLYSTIM study. Results: Compared with BMT, DBS resulted in significantly greater improvements from baseline through 24 months in social, occupational, and psychosocial functioning. Yet, work status in the 2 groups did not differ at baseline and 24 months. Physicians reported a significantly higher percentage of patients in the BMT group unable to work at 24 months relative to baseline compared with the DBS group. Apathy was significantly worse in patients for whom physicians overrated ability to work when compared with patients' own ratings than in the group of patients who physicians' ability to work ratings were comparable to, or worse than, patients' self‐ratings of ability to work. Conclusions: For patients aged ≤60 years with PD and early motor complications, DBS provided significant improvements in social, occupational, and psychosocial function, but not in the actual work engagement compared with BMT at 2 years. Apathy may impact ability to work.